(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2026)
Artificial intelligence is becoming a fully-fledged tool of diplomacy. Algorithms warn of conflicts before they break out and simulate dozens of peace treaty scenarios in a matter of hours. But can machines trained on human data overcome our own biases? Is the world truly on the brink of a revolution in international relations.